2018
DOI: 10.1039/c7nr07100k
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-orientation dependent epitaxial growth of highly ordered diamond nanosheet arrays by chemical vapor deposition

Abstract: Three-dimensional ordering of two-dimensional nanomaterials has long been a challenge. Simultaneously, diamond nanomaterials are difficult to synthesize due to the harsh synthesizing conditions required. Here, we report substrate-crystal-orientation dependent growth of diamond nanosheets (DNSs) by chemical vapor deposition, which generates different DNS arrays on different substrates. The DNSs are grown by the in-plane epitaxy of the diamond {111} planes. So the arrays are highly ordered and solely determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
4
18
0
1
Order By: Relevance
“…The structure and composition of the samples were characterized by the methods described in our previous reports. , A resistance measuring system (2182A, Keithley) was used to determine the electrical conductivity of the samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure and composition of the samples were characterized by the methods described in our previous reports. , A resistance measuring system (2182A, Keithley) was used to determine the electrical conductivity of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al have used Ni, Fe, or Au/Ge films as catalysts to prepare the diamond nanosheets by microwave plasma chemical vapor deposition (MPCVD). Later, the same group also prepared the diamond nanosheets on nanocrystalline diamond substrates without using catalysts . In 2008, Raina et al prepared the vertical diamond nanosheets (ridge profile) by introducing N 2 during the growth process. , Recently, we revealed that the diamond nanosheets arise from epitaxial growth of {111} planes of diamond substrates, resulting in the formation of highly ordered nanosheets arrays . Generally, the diamond nanosheets are grown accompanied by the graphitic overlayers, forming a diamond/graphite core/shell hybrid structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pengendapan uap polimer dan substrat Pengendapan uap polimer telah membuka pintu ke berbagai bahan yang akan sulit, dan dalam beberapa kasus dan tidak mungkin, untuk diproduksi dengan cara lain. Sebagai contoh, banyak polimer yang bermanfaat, seperti bahan penumpahan air untuk melindungi komponen industri atau implan biologis, dibuat dari prekursor yang tidak dapat larut, sehingga tidak dapat diproduksi menggunakan metode berbasis solusi konvensional (90)(91)(92)(93). Pekerjaan Gleason pada CVD berbasis polimer dimulai pada 1990-an, ketika dia melakukan eksperimen dengan Teflon, senyawa klorin dan fluor.…”
Section: A Proses Chemical Vapor Deposisiunclassified
“…In this paper, we report the structure of another low-index surface of the Ba 8 Au 5.25 Ge 40.75 clathrate. Surface orientations play an important role in a wide range of applications, such as crystal growth, , wet etching, self-assembly, , and catalysis. , Investigations of the surface structures as a function of the surface orientations are then required to better control and achieve the desired surface chemistry and functionality.…”
Section: Introductionmentioning
confidence: 99%